Pengendalian Stunting dan Gizi Buruk di Desa Punti Kecamatan Soromandi Melalui Optimalisasi Posyandu - Sulistianingsih Sulistianingsih; Triati Putri; Risman Risman; Nurul Putri; Nur Iklimah; Ummu Aiman; Gilang Ramadhan; Ismunandar Ismunandar; Muhammad Badar (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
Stunting and malnutrition are critical issues affecting children in rural areas, including Desa Punti, Kecamatan Soromandi. This community service program aimed to optimize the role of Posyandu (Integrated Service Post) in addressing stunting and improving nutritional awareness among mothers. The methods included participatory community engagement, nutrition education, and monthly health check-ups for children under five. Results showed increased community participation, improved child nutritional status, and enhanced health knowledge among mothers. These findings highlight the potential of Posyandu as a cornerstone for preventive health measures. Further efforts are needed to sustain these initiatives through local stakeholder collaboration.